PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN TIDAK DAPAT DITERIMA (NIET ONTVANKELIJKE VERKLAARD) DALAM PERKARA WANPRESTASI DI PENGADILAN NEGERI PADANG KELAS 1A (Studi Putusan Perkara No. 92/Pdt.G/2023/PN PDG) - Bambang Hermanto, Abd. Rahmad dan (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
In the civil law system, a civil lawsuit can be filed by a party who feels aggrieved by an act committed by another party. The lawsuit filed by the plaintiff named Nova Sikma Yenti to the Padang District Court alleges an unlawful act for the defendant's installation of a banner that reads